Anxiety symptoms and coping strategies used by older adults during COVID-19: a national e-study of linkages among and between them - Low, Gail; França, Alex B.; Gao, Zhiwei; Gutman, Gloria; von Humboldt, Sofia; Allana, Hunaina; Wilson, Donna M.; Naz, Anila (My University, 2025)
A global pandemic is a hardly typical and anxiety-dampening event. Research in the first year of the COVID-19 pandemic tells of associations between advancing age and anxiety dampening. The aim of this study was to further investigate this by examining and creating a blueprint of older Canadians’ symptoms of pandemic-related anxiety and coping strategies, and linkages among and between them. A national e-survey was conducted in the second year of the pandemic with 1,327 older Canadians, when national public health measures lifted. Anxiety symptoms were measured using the Geriatric Anxiety Scale - 10. Participants also completed the Coping with Stress and Anxiety personal assessment tool. Network Analyses revealed a troubling trio of anxiety symptoms of central importance to our respondents: feelings of restlessness, muscle tension and having no control over their lives. Restless and no control over my life explained between 64–68% of the variance in 8 other anxiety symptoms. Coping seemed to occur through trial and error. Some strategies appeared to work in tandem and others in opposition to each other. Remembered resilience and staying active functioned as bridges shielding older people from worry, restlessness, and tension through spurning other remedial actions. This study provides evidence of a stable and predictable network of anxiety symptoms containing three particularly pernicious symptoms and the complex and arduous nature of mentally healthy recovery work. A visual representation of how anxiety symptoms can operate as a network might help older people better understand their own symptom experiences. Combining the two networks offers a blueprint of what within-person recovery might look like and a visual teaching tool for practitioners and program developers; older people could gain added insight into their own recovery experience.
Keywords: COVID-19 pandemic; anxiety-dampening event; pandemic-related anxiety; strategies; older Canadians